2019
DOI: 10.1038/s41598-019-42432-2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet proteome reveals specific proteins associated with platelet activation and the hypercoagulable state in β-thalassmia/HbE patients

Abstract: A hypercoagulable state leading to a high risk of a thrombotic event is one of the most common complications observed in β-thalassemia/HbE disease, particularly in patients who have undergone a splenectomy. However, the hypercoagulable state, as well as the molecular mechanism of this aspect of the pathogenesis of β-thalassemia/HbE, remains poorly understood. To address this issue, fifteen non-splenectomized β-thalassemia/HbE patients, 8 splenectomized β-thalassemia/HbE patients and 20 healthy volunteers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The potentially toxic unstable free α-globin chains in βThal + RBCs can be eliminated by functionally interconnected protein quality control pathways [ 26 ]. It has been suggested that chaperones may be involved in α-globin refolding or targeting for degradation to proteasome [ 12 , 27 , 28 , 29 ], and, consequently, numerous molecular chaperones are upregulated in βThal + trait erythroblasts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The potentially toxic unstable free α-globin chains in βThal + RBCs can be eliminated by functionally interconnected protein quality control pathways [ 26 ]. It has been suggested that chaperones may be involved in α-globin refolding or targeting for degradation to proteasome [ 12 , 27 , 28 , 29 ], and, consequently, numerous molecular chaperones are upregulated in βThal + trait erythroblasts in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, platelet functions were prominently affected, including platelet activation, platelet aggregation, platelet degranulation, and response to elevated platelet cytosolic Ca 2+ . Platelet activation ( Fayed et al., 2018 ) and aggregation ( Winichagoon et al., 1981 ) observed in patients with β-thalassemia are risk factors for hypercoagulopathy, resulting in thromboembolic events ( Cappellini et al., 2012 ; Chanpeng et al., 2019 ). In the above-mentioned platelet modules, we also observed a significant upregulation of pleckstrin (PLEK), whose intronic polymorphism is an independent genetic risk factor for venous thromboembolism ( Lindstrom et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry (MS)-based proteomics has become a powerful approach for the exploration of biomarkers or pathophysiological characteristics in various diseases ( Shen et al., 2020 ; Tewari et al., 2018 ; Wewer Albrechtsen et al., 2018 ). Previous studies of the proteomics profile of patients with β-thalassemia reported dysregulated proteins associated with the key pathological conditions implicated in thalassemia, including oxidative stress ( Ponnikorn et al., 2019 ), hemolysis ( Kittivorapart et al., 2018 ), and the hypercoagulable state ( Chanpeng et al., 2019 ) when compared with healthy individuals. Several proteins correlating with the disease, for example, haptoglobin, hemopexin, and cathepsin S, were proposed as potential clinically relevant biomarkers ( Kittivorapart et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although we focused on proteins that are increasingly synthesized after activation, protein secretion and vesiculation from platelets is another important biological event that affects the intracellular set of platelet proteins besides the proteomic regulation mechanisms described above. Platelets store a huge variety of vasoactivate proteins in preformed vesicles which are rapidly released with activation and which may then be lost for analysis and change the proteome of activated platelets [ 30 , 31 , 32 , 33 ]. All proteins that we discuss in this study have been shown to be involved in the regulation of cell migration and mobility: gelsolin is critical for actin assembly/disassembly and podosome formation [ 34 ], vinculin for focal adhesion dynamics [ 35 ], coronin for dynamic F-actin binding [ 36 ], kindlin-3 ( FERMT3 ) [ 37 ] and talin 1 are critical in signal transfer between integrins and the cytoskeleton, while filamin A [ 38 ] is essential for the interaction between membranes and actin fibers.…”
Section: Discussionmentioning
confidence: 99%